Preventive Protection for Indonesian Migrant Workers as Part of an Effort to Prevent Human Trafficking in Johor Bahru Malaysia - Suci Flambonita; Vera Novianti; Artha Febriansyah (Borong Newinera Publisher, 2022)
The issues of Indonesian migrant workers are interminable; practically all bordering countries, including Malaysia, are destinations for Indonesian migrant workers. Administrative issues, salary disparities, exploitation, and human trafficking are all issues that Indonesian migrant workers encounter abroad. As the country's representative, the Embassy/Consulate General of the Republic of Indonesia plays a vital role in defending Indonesian migrant workers and Indonesian nationals overseas. The government's legal protection normally begins with document registration, followed by preparation, training, and placement. This study used a normative strategy with a statutory and case approach. Preventive protection takes the form of providing protection based on Law Number 21 of 2007 about TIP, Law Number 18 of 2017 concerning PMI Protection, and Malaysian Law in Deed 670 concerning the Anti-Trafficking in Persons and Anti-Migrant Smuggling Deed 2007. The Consulate General of the Republic of Indonesia Malaysia provides legal protection for Indonesian employees who are victims of illegal acts of human trafficking through both litigation and non-litigation routes.